The Effect of Marketing Mix on Purchase Decisions for PAS Leather Products in Magetan Regency in 2022 - Fergiawan Alfianto Rizkaputra; Alun Pratama; Wira Ganet Aribowo; Handaru Agnyana (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
This study aims to analyze the effect of the Marketing Mix on Purchase Decisions for Pas Leather Products in Magetan Regency. This study uses a quantitative approach. The sample of this research is 100 consumers. The method of collecting data is distributing questionnaires given to respondents online. Data analysis using multiple linear analysis. The results of the study explained that (1) the product variable had a positive and significant effect on purchasing decisions, (2) the distribution channel variable had a positive and significant effect on purchasing decisions, (3) the promotion variable had a positive and significant effect on purchasing decisions, (4) the price variable did not positive and significant effect on purchasing decisions. The results of this study can be used as a reference by SMEs for business development, especially in the leather fashion industry.